Blendas de poli(óxido de etileno) com diferentes amidos : avaliação da miscibilidade e da velocidade de crescimento de esferulitos - Pereira, Antonio Guilherme Basso (2008)
Blends based on poly(ethylene oxide) Mn = 200 kg Mol-1 and different starches (unmodified, cationic and hydrophobic) (100/0, 95/05, 90/10, 80/20, 70/30, 65/35 and 60/40 ratios) obtained by casting from aqueous solution were investigated. The main purposes were evaluating the influence of starch (type and amount) on the miscibility and their effect in the spherulite growth rate of PEO. By thermal analysis (DSC) and by the use of the Nishi-Wang equation a negative value (= -0.25) for the interaction parameter for PEO/unmodified starch was obtained. This analysis based in the depression on the equilibrium melting temperature, (...). So, this system was considered as miscible, exception for the 95/05 blend ratio, in which an increase in (...) relative to pure PEO was observed. By the FTIR spectra analysis it was possible to identify two distinct phases on PEO/unmodified starch 95/05 blend ratio because some characteristics vibration modes of starch (COC and COH at ca. 1000 cm-1) appear in one region and are absent in another region of spherulite. Besides, the images from SEM for this blend ratio showed very similar morphology relative to pure PEO. The morphology of PEO/unmodified 90/10 blend ratio is significantly different of 95/05 one. These results suggest that there is a miscibility window on PEO/unmodified starch in the range from 90/10 to 65/35 that was confirmed by Raman, WAXS and SEM. For PEO/hydrophobic starch blends, a negative value (-0.63) for the interaction parameter was obtained (-0.63). The miscibility of this system in the range of studied (95/05 - 60/40) was ratified by other techniques (WAXS, SEM). For PEO/cationic starch, a positive value (0.68) for the interaction parameter was obtained showing that PEO/cationic starch blends should be immiscible. This evidence was confirmed by WAXS and SEM images of blends. By the use of optical microscope it was concluded that the properties such as spherulite growth rate and miscibility can be significantly altered by changing the amount and the type of starches. The results obtained in this dissertation can be used for helping the development of scaffolds, mainly between 80/20 and 65/35 ratios PEO/unmodified starch, for using on cell cultures and tissue engineering and other biomaterials issue.